2006
DOI: 10.1196/annals.1378.094
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Leptin Antagonists by Site‐Directed Mutagenesis of Human, Ovine, Rat, and Mouse Leptin's Site III

Abstract: Six muteins of human, ovine, rat, and mouse leptins mutated to Ala in amino acids 39-41 or 39-42 were prepared by site-directed mutagenesis of the putative site III, which does not affect binding but is necessary for receptor activation, then expressed, solubilized in 4.5 M urea, at pH 11.3 in presence of cysteine, refolded and purified to homogeneity by anion-exchange chromatography on Q-Sepharose or combination of anion-exchange chromatography followed by gel filtration. The overall yields were 400-800 mg fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Our hypothesis was that leptin might be a cytokine involved in the maturation of the whole organism during the neonatal period. The recent availability of competitive leptin antagonists 16 has opened new opportunities to clarify the physiological role of leptin during specific periods of life. We previously demonstrated that the specific blockage of leptin action between postnatal days 2 and 13 resulted in a longterm alteration of food intake regulation and a higher susceptibility to diet-induced obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis was that leptin might be a cytokine involved in the maturation of the whole organism during the neonatal period. The recent availability of competitive leptin antagonists 16 has opened new opportunities to clarify the physiological role of leptin during specific periods of life. We previously demonstrated that the specific blockage of leptin action between postnatal days 2 and 13 resulted in a longterm alteration of food intake regulation and a higher susceptibility to diet-induced obesity.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, we used a polyethylene glycol (PEG)ylated mouse leptin antagonist (PEG-MLA) (mutant L39A/D40A/F41A) that binds, but does not activate, the leptin receptor (38) to disrupt endogenous leptin signaling in adult wild-type mice. Peripheral administration of PEG-MLA competes with endogenous leptin binding in the periphery and blocks transport of leptin across the blood brain barrier (39).…”
mentioning
confidence: 99%
“…The objective of the studies described here was to test whether forebrain and hindbrain leptin receptors have different effects on body composition. This was accomplished by chronically infusing low doses of leptin into either the 3rd or the 4th ventricle of rats or by infusing the rats peripherally with leptin while inhibiting activation of forebrain or hindbrain receptors by infusion of the leptin receptor antagonist leptin mutein protein (mutein) (42) into the 3rd or 4th ventricle.…”
mentioning
confidence: 99%